A theoretical model of disease - Peña, Adolfo (2003)
This paper outlines the concept of disease as a theoretical model, that is, a schematic conceptual representation to describe disease in theoretical terms (of high generality). We will utilize mathematical concepts, such as set and function, and general theories like the general systems theory and emergentist materialism.